2004
DOI: 10.1158/1078-0432.ccr-03-0508
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Bortezomib in Refractory or Relapsed Acute Leukemias

Abstract: Bortezomib (Velcade, formerly PS-341) is proteasome inhibitor with documented antitumor activity in multiple myeloma and other lymphoid malignancies. We performed a Phase I study to investigate the maximum tolerated dose and dose-limiting toxicity of bortezomib in patients with acute leukemias refractory to or relapsing after prior therapy. Fifteen patients were treated with 0.75 (n ‫؍‬ 3), 1.25 (n ‫؍‬ 7), or 1.5 (n ‫؍‬ 5) mg/m 2 bortezomib administered twice weekly for 4 weeks every 6 weeks. Dose-limiting tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 24 publications
4
113
0
Order By: Relevance
“…In comparison, maximal whole blood CT‐L inhibition in several clinical studies with BTZ was reported to be 65–69% by either the intravenous or subcutaneous routes of administration on a twice‐weekly schedule (Cortes et al , 2004; Dy et al , 2005; Moreau et al , 2008), although sporadic individuals with up to 84% CT‐L reduction have been described (Reece et al , 2011). CFZ is a highly potent, irreversible and specific inhibitor of the CT‐L subunit (Kuhn et al , 2007) and, accordingly, was able to block 75% of CT‐L activity after one dose (O'Connor et al , 2009) in whole blood or PBMCs and up to 80–90% after repeat dosing (Alsina et al , 2012), although the most impressive activity was seen on an unapproved schedule of five daily doses (O'Connor et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, maximal whole blood CT‐L inhibition in several clinical studies with BTZ was reported to be 65–69% by either the intravenous or subcutaneous routes of administration on a twice‐weekly schedule (Cortes et al , 2004; Dy et al , 2005; Moreau et al , 2008), although sporadic individuals with up to 84% CT‐L reduction have been described (Reece et al , 2011). CFZ is a highly potent, irreversible and specific inhibitor of the CT‐L subunit (Kuhn et al , 2007) and, accordingly, was able to block 75% of CT‐L activity after one dose (O'Connor et al , 2009) in whole blood or PBMCs and up to 80–90% after repeat dosing (Alsina et al , 2012), although the most impressive activity was seen on an unapproved schedule of five daily doses (O'Connor et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the clinical success of proteasome inhibitors in two hematologic malignancies (myeloma and mantle cell lymphoma), considerable interest exists in expanding the use of proteasome inhibitors to leukemias and other lymphomas. Unfortunately, bortezomib did not exert substantial clinical activity in these other hematologic malignancies (15), prompting studies to examine other proteasome inhibitors and to understand better the role of the proteasome in leukemia biology.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…In this setting, bortezomib (Velcade) was demonstrated to be effective in the treatment of multiple myeloma and non-Hodgkin's lymphoma, when taken alone or in combination with traditional anticancer drugs [3][4][5][6][7]. Similarly, preliminary studies indicated that proteasome inhibitors induce clinical responses in patients with acute leukemia, prostate cancer, renal cell carcinoma, neuroendocrine tumors, and in children solid tumors [8][9][10][11][12]. How proteasome inhibition translates into a potent cytotoxic effect in tumor cells is not fully understood, even though inhibition of NF-jB and deregulated expression of p53, caspases, Bcl-2 family members, CDC25 family proteins and cyclins were all proposed to be relevant in this context [1,2].…”
Section: Introductionmentioning
confidence: 99%